Facilitating a Collaborative Approach to E-Learning for Program Planners, Instructor Training and Technology Leadership - Sandra Ratcliff Daffron; Sarah DiRuscio; Ed Webster (Adult Education Research Conference, 2010)
Significant differences in expertise and attitudes towards e-learning technology are not uncommon between those who design the program and maintain the technology (program planners and technicians) and those who use the resources and technology (instructors and trainers). This wide disconnect between the two groups will often result in frustration and a poor quality product. Models of e-learning training and collaboration will be illustrated in three settings: higher education, secondary education, and the corporate level.